Effect of Electrocoagulational, Cryo- and Ultrasound Treatment of the Gallbladder Bed After Experimental Cholecystectomy - Khvorostov, Yevgen; Bychkov, Sergii; Tsivenko, Olexii; Cherkova, Nataliia; Dushyk, Liudmyla (Problems of Cryobiology and Cryomedicine, 2020)
The results of electron microscopic examination of reparative processes in liver tissue of rabbits after cholecystectomy performed with monopolar electrocoagulation, ultrasonic scalpel and at low temperatures on days 1, 3, 14, 21 and 30 were comparatively analyzed. Experimental findings allowed to compare the hemo- and cholestatic effects of different types of energy, to assess the degree of trauma to the liver parenchyma in the surgery area and the impact of different methods on the quality and timing of repair. Ultrastructural changes in hepatocytes depending on the methods of influence were characterized with various dystrophic and destructive processes. Electron microscopic studies showed that the ultrastructure of liver cells after electrocoagulation on the bed of the removed gallbladder corresponded the norm on day 30, after cryoeffect it did on day 21, and after ultrasound this was on day 14. It has been proven that the use of ultrasound and cryoeffect in cholecystectomy compared to electrocoagulation occurred to be the least traumatic for liver tissue. Â  Probl Cryobiol Cryomed 2020; 30(2): 178-187